Legal and social viability of polygamy : an analysis - Ansari, Abdul Haseeb; Md Hassan Ahmed, Kyaw Hla Win (International Islamic University Malaysia, 2011)
In Islam, a Muslim male is allowed to have up to four wives provided all wives are treaty equally and do not suffer from any kind of discrimination. The divine injunction of equal treatment is actually for protecting rights of the wives. It is for this reason that many Muslim countries have enacted laws for providing protection to wives. One of the notable legal principles is that a man, who has a wife, cannot marry with another female without permission of the first wife, and so on; or he can do so if allowed by the court of competent jurisdiction. Some other countries, like Tunisia, have banned polygamy. This, in effect, is denial to the right guaranteed in the SharÊ‘ah to both Muslim males and females, as in certain circumstances polygamy brings happiness to the family. For example, if wife is suffering from some kind of contagious disease and the husband is deprived of fulfilling his sexual desire, in view of the ban, he will have to divorce his first wife in order to marry with some other female. In India, in such a situation, there are reports that the firs wife, who is already in agony of a disease, is either burned or divorced on the basis of mutual consent, which is generally based on duress or payment of inappropriate amount of money. This is violation of matrimonial rights guaranteed by the SharÊ‘ah and constitutions of modern states. The paper discusses the human right aspect of polygamy referring to various religious positions and law in some Muslim countries. The paper concludes that polygamy should be allowed but law should be designed in such a way that the divine injunction of equal treatment of all wives is ensured.